The Effect of Product Quality and Service Quality on Customer Satisfaction at Story Coffee - Sagita, Olip; Alam, Iskandar Ali (CV. Rayyan Dwi Bharata, 2025)
The aim of this research is to examine the impact of product quality and service quality on customer satisfaction at Story Coffee, a coffee shop located in Mesuji, Lampung. The method used is quantitative, where questionnaire data is distributed to 100 respondents. Using multiple linear regression is a method for reviewing data using SPSS software. The results of this research show that product quality and service quality have a positive and significant impact on customer satisfaction. And influenced by other factors that were not studied. Product quality factors include taste, freshness and appearance of the product, while service quality includes speed of service, friendliness of staff and cafe atmosphere. The conclusion of this research shows the importance of maintaining product and service quality standards to increase customer satisfaction which has an impact on loyalty and business sustainability.